P323 Prognostic factors for long-term adalimumab treatment. (25th January 2019) - Fumery, M; Duveau, N; Perignon, C; Lepeut, G; Lahaye, A; Le Baut, G; Roussillon, C; Yzet, C; Loreau, J; Wils, P; Nachury, M; Pariente, B; et al.
Abstract: Background: Adalimumab is widely used in the treatment of patients with Crohn's disease (CD), either as first- and second-line therapy. However, data concerning the treatment persistence of adalimumab in patients with CD are scarce. Aims of the present study were (1) to evaluate the rate of primary non-response to adalimumab (PNR, defined by a withdrawal of adalimumab before the fourth month of treatment), (2) to evaluate the treatment persistence rates of adalimumab during the follow-up, and (3) to identify factors associated with PNR and adalimumab persistence in CD patients. Methods: We performed a retrospective study in from January 2012 to December 2017 in the three tertiary centres of Amiens, Caen, and Lille in France. All consecutive CD patients treated with adalimumab were analysed. Only patients who received a full adalimumab induction treatment were considered. Survival analyses were performed using the Kaplan–Meier method. Patient- and disease-related factors were used to identify independent predictors of PNR and of adalimumab failure-free survival using Cox proportional hazards regression. Results: Between January 2012 to December 2017, 405 patients with CD received a full induction of adalimumab treatment. At adalimumab introduction, 41% were female, median age was 31[IQR: 24–44] years, median disease duration was 6 [IQR: 1–14] years and 30% of patients had a BMI ≥ 25 kg/m 2 (overweight and obese patients). 136 (34%) patients previously received infliximab treatment: 12% stopped infliximab for PNR, 49% for secondary loss of response (LOR), and 37% for intolerance, and 2% for other reasons. Median time on adalimumab was 1.7 [IQR: 0.7–3.6] years, and 226 (55%) patients experienced adalimumab failure. Seventy-five (16%) underwent major abdominal surgery and 102 (26%) were hospitalised during the follow-up. Thirty-eight (9%) patients had a PNR to adalimumab and 367 (91%) patients maintained scheduled adalimumab treatment. Adalimumab failure-free survival rates were 76% at 12 months, 59% at 24 months and 51% at 36 months. Multi-variate Cox regression identified disease duration ≥ 2 years [HR 3.16 (95% CI 1.15–1.85), p = 0.02] and previous infliximab treatment [HR 2.38 (1.09–2.57), p = 0.017] as independent predictors of adalimumab failure survival. Conclusions: In this large study of CD patients, more than half of the patients maintained adalimumab at 3 years. Patients with early CD, naive of anti-TNF treatments exhibited the best profile to response to adalimumab treatment. Awaiting results from disease modifications trials, these results suggest the clear benefit of introducing biologics early in the disease history.